The Strategic Role of KLL UMSIDA in Graduating Thousands of Scholars: Peran Strategis KLL UMSIDA dalam Meluluskan Ribuan Sarjana - Kusuma, Kumara Adji; Hidayatulloh (Universitas Muhammadiyah Sidoarjo, 2024)
The Institution of Amil Zakat Infaq and Sadaqah Muhammadiyah (Lazismu) have a vital role in the economic development of the Ummah (Muslim Society) in Indonesia. In this context, Indonesia state which constitutionally gets the main mandate in Article 34 of the 1945 Constitution to improve the welfare of the people of Indonesia is not so significant in carrying out this function with many poor people who have not been alleviated in terms of economy, health or education. Lazismu then equips with a strategic role in efforts to become a back-up solution for the Indonesian state. As part of the Ummah and nation Lazismu becomes a solution, more specifically in the context of this research the object is the Lazismu Service Office (KLL) Muhammadiyah University of Sidoarjo (UMSIDA) in increasing the level of education of the ummah. Through the Lazismu scholarship program Sang Surya, more than a thousand students of higher education managed to continue and complete their undergraduate education. This scientific work in a descriptive phenomenological way reveals the strategic role of the UMSIDA KLL in graduating scholars in Indonesia. It is hoped that this research can become a benchmark for other campuses to take the same role in graduating scholars through zakat infaq and shadaqah funds.